2017
DOI: 10.1080/1343943x.2017.1279528
|View full text |Cite
|
Sign up to set email alerts
|

MYB and HD-ZIP IV homologs related to trichome formation are involved in epidermal bladder cell development in the halophyteMesembryanthemum crystallinumL.

Abstract: The common ice plant, Mesembryanthemum crystallinum L., a halophytic new functional leafy vegetable crop, develops epidermal bladder cells (EBCs) on the surfaces of its aerial organs. Our previous studies of the physiological characteristics of the wild-type and the EBC-less mutant indicated that EBCs sequester salt and maintain ion homeostasis within photosynthetically active tissues. The EBC has been thought to be a modified trichome; however, molecular mechanisms governing EBC development in the common ice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…A positive correlation between the presence and/or the number of EBCs and salt tolerance was reported in Chenopodium quinoa [ 74 , 78 ]. Some candidate genes related to EBC formation were recently identified using transcriptome analysis in C. quinoa , Mesembryanthemum crystallinum, and Atriplex centralasiatica species [ 79 , 80 , 81 ] ( Table 1 ). More fundamentally, Imamura et al [ 82 ] first identified a gene, named reduced epidermal bladder cells ( REBC ), involved in the EBC development in C. quinoa , laying the foundation for elucidating the EBC-associated stress tolerance mechanism in halophytes.…”
Section: Physiological Mechanisms Associated With Halophyte Adaptation To Soil Salinitymentioning
confidence: 99%
“…A positive correlation between the presence and/or the number of EBCs and salt tolerance was reported in Chenopodium quinoa [ 74 , 78 ]. Some candidate genes related to EBC formation were recently identified using transcriptome analysis in C. quinoa , Mesembryanthemum crystallinum, and Atriplex centralasiatica species [ 79 , 80 , 81 ] ( Table 1 ). More fundamentally, Imamura et al [ 82 ] first identified a gene, named reduced epidermal bladder cells ( REBC ), involved in the EBC development in C. quinoa , laying the foundation for elucidating the EBC-associated stress tolerance mechanism in halophytes.…”
Section: Physiological Mechanisms Associated With Halophyte Adaptation To Soil Salinitymentioning
confidence: 99%
“…Furthermore, 57 of 92 genes upregulated by at least 2-fold in the mutant were also expressed in EBCs (Supplementary Data 4). Next, we compared the genes with altered expression in rebc mutants were compared with those whose expression was altered in a mutant form of M. crystallinum that lacked EBCs 13,14 . A gene belonging to the jasmonate-induced protein family was downregulated in both M. crystallinum (WM28; NCBI Acc.…”
Section: And Supplementarymentioning
confidence: 99%
“…Although physiological analysis has elucidated some aspects of EBC function 9,10 , no studies to date have investigated how EBCs develop. Recently, some candidate genes related to EBC formation were selected in M. crystallinum 13,14 . However, because the key genes involved in EBC formation have not yet been isolated, the molecular mechanism underlying the formation of these important cells remains unknown.…”
mentioning
confidence: 99%
“…Soil salinization is an increasingly significant factor affecting plant growth and crop productivity. It is reported that salinity decreases the average yields of major crops by more than 50% (Bray et al , Roeurn et al ). Numerous mechanisms that regulate the transcription of HD‐Zip I genes involved in response to salt stress have been studied (Shen et al 2003, Ariel et al , Li et al , , Bhattacharjee et al , Wu et al , Zhang et al ).…”
Section: Aba‐mediated Stress Responsementioning
confidence: 99%